Three-dimensional graphene–Co3O4 cathodes for rechargeable Li–O2 batteries. Issue 4 (1st December 2014) - Zhang, Jiakai; Li, Pengfa; Wang, Zhenhua; Qiao, Jinshuo; Rooney, David; Sun, Wang; Sun, Kening
Abstract : A three-dimensional (3D) graphene–Co3 O4 electrode was prepared by a two-step method and this binder-free monolithic electrode exhibited enhanced performance for rechargeable Li–O2 batteries. Abstract : A three-dimensional (3D) graphene–Co3 O4 electrode was prepared by a two-step method in which graphene was initially deposited on a Ni foam with Co3 O4 then grown on the resulting graphene structure. Cross-linked Co3 O4 nanosheets with an open pore structure were fully and vertically distributed throughout the graphene skeleton. The free-standing and binder-free monolithic electrode was used directly as a cathode in a Li–O2 battery. This composite structure exhibited enhanced performance with a specific capacity of 2453 mA h g −1 at 0.1 mA cm −2 and 62 stable cycles with 583 mA h g −1 (1000 mA h gcarbon −1 ). The excellent electrochemical performance is associated with the unique architecture and superior catalytic activity of the 3D electrode.